Public Private Affairs in the Correspondence Between the Signatory of the Act of Independence Jurgis Šaulys (1879–1948) and Gabrielė Petkevičaitė- Bitė - Plečkaitis, Vytautas Petras (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English] Jurgis Šaulys, one of the most outstanding personalities of the Lithuanian national revival of the late 19th century–first half of the 20th century, left a deep mark on the Lithuanian culture, diplomacy, and politics. Alongside with Kazys Grinius, Jonas Vileišis, Povilas Višinskis and others, he stood at the origins of the Democratic Party, edited the Lithuanian newspaper Varpas and other periodicals, wrote a lot on public, political and cultural issues and left a deep imprint on Lithuanian literary criticism. While studying economics and finance at the University of Bern in 1903–1912, he did not discontinue his public activities and journalistic work. Šaulys corresponded with prominent personalities of the Lithuanian national revival; he did not only write letters to Lithuanians but also wrote to the Polish Vilnius press; while on vacation, he would come back from Switzerland to his homeland to participate in the excavations of Lithuanian hillforts. After graduation from the University of Bern with a doctorate in finance, Šaulys returned to Vilnius and found placement at the Vilnius Land Bank as well as took an active part in the public national life. At the Vilnius Seimas held in September 1917 he was elected to the Council of Lithuania and declared the Act of Independence of Lithuania of 16 February 1918 together with its 20 members. During the period of the Republic of Lithuania he became the first officially approved diplomat of his country; he represented Lithuania’s interests in the capacity of an ambassador in Germany, Switzerland, Italy, the Holy See, and Poland. In pre-war Lithuania Jurgis Šaulys was known as a dedicated bibliophile; he had accumulated a rich library of Lithuanian literature; he was a connoisseur of arts and culture. The article discusses the correspondence between Jurgis Šaulys and a prominent Lithuanian public figure, writer Gabrielė Petkevičaitė-Bitė. Together with other nationally-spirited educated women, she organised the society Žiburėlis which intended to support talented poor pupils and students abroad because after Vilnius University was closed by the Tsarist government in 1832, there were no schools of higher education in Lithuania. Thanks to Petkevičaitė-Bitė, Šaulys received a scholarship as well as excellent education in the West. He was one of the first participants in the Lithuanian national revival movement to receive a doctorate in the West. The correspondence between Šaulys and Petkevičaitė continued for about 20 years. Her letters to Šaulys contain a number of interesting facts in relation to both Šaulys’ public activities and the twists and turns of his personal life enabling a better understanding of his period as well as his personality and the people he communicated with.